Sleep therapy in history - Stucchi-Portocarrero, Santiago (2020)
At the end of the 19th century, substances such as bromides began to be used to induce deep sleep in people with mental disorders. The use of barbiturates for the same purpose was reported by Epifanio in 1913, but it was Kläsi, in the early 1920s, who most successfully fostered the administration of such agents, particularly Somnifen, for what he called “sleep cure” or “prolonged narcosis” (dauernarkose). In 1934 Cloettal, a mixture of barbiturates and other compounds, was introduced to replace Somnifen. The use of this procedure declined with the appearance of other therapeutic methods, but continued for several decades. In the Soviet Union, sleep cure was influenced by the Pavlovian doctrine, and used for both mental disorders and conditions considered as psychosomatic. The method’s greatest discredit occurred at Chelmsford Hospital in Australia, where 25 deaths associated with its use were reported during the period 1963-1979. In 2009, the Royal College of Psychiatrists of Australia and New Zealand concluded that “deep sleep therapy and the administration of intravenous barbiturates has no place in the treatment of psychiatric disorders”. Even though, currently it is not part of any conventional treatment, sleep cure is still offered and requested.